2011
DOI: 10.1016/j.jsr.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Reducing fall risk by improving balance control: Development, evaluation and knowledge-translation of new approaches

Abstract: Our findings support the efficacy of the developed balance-training methods, balance-enhancing footwear, neuro-prosthesis, walker design, handrail-cueing system, and handrail-design recommendations in improving specific aspects of balance control. IMPACT ON KNOWLEDGE USERS: A new balance-assessment tool has been implemented in the first new balance clinic, a new balance-enhancing insole is available through pharmacies and other commercial outlets, and handrail design recommendations have been incorporated into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 96 publications
2
36
0
1
Order By: Relevance
“…Such slowness did not seem to be caused by a limitation in the ability to move the COM quickly, since the velocity of the COM motion in FR did not show significant age effect. Moving the COM more slowly has been found when older adults were required to walk under more challenging conditions (Buracchio et al 2011;Maki et al 2011;Renfro and Fehrer 2011;Tsai and Lin 2013). Thus, the slowness observed in older adults in this study was likely to be a strategy specifically adopted to meet the increased task demand associated with UR.…”
Section: Discussionmentioning
confidence: 60%
“…Such slowness did not seem to be caused by a limitation in the ability to move the COM quickly, since the velocity of the COM motion in FR did not show significant age effect. Moving the COM more slowly has been found when older adults were required to walk under more challenging conditions (Buracchio et al 2011;Maki et al 2011;Renfro and Fehrer 2011;Tsai and Lin 2013). Thus, the slowness observed in older adults in this study was likely to be a strategy specifically adopted to meet the increased task demand associated with UR.…”
Section: Discussionmentioning
confidence: 60%
“…It is suggested that there is a statistically significant relationship between patient falls and problems such as impaired gait, weakness, decline in lower extremity function, balance, and coordination problems (Carson & Cook, 2008;Maki et al, 2011;O'Sullivan & Schmitz, 2001;Oliver et al, 2010;Taylor et al, 2012). Falls are one of the most common complications of many neurological diseases such as stroke, multiple sclerosis, and Parkinson's (Soyuer, Soyuer, & € Ozt€ urk, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers designed a semi-structured interview form by using open-ended questions based on related literature. (Bemis-Dougherty & Delaune, 2008;Carson & Cook, 2008;Dacenko-Grawe & Holm, 2008;Evans, Hodgkinson, Lambert, Wood, & Kowanko, 1998;Fischer et al, 2005;Forrest et al, 2012;Maki et al, 2011;Mion et al, 2012;Oliver et al, 2010). The nurses were expected to respond to the following questions in the semi-structured interview form.…”
Section: Data Collectionmentioning
confidence: 99%
“…Falling often has a complex form; it is defined as lying on the ground or at a lower level by accident, except conscious positional change for resting on seats, walls, or other objects, and is affected by multiple factors [93][94][95][96]. There are different descriptions, such as intrinsic and extrinsic factors, associated with the risk factors of falling [94,95].…”
Section: Falling and Fear Of Fallingmentioning
confidence: 99%